2015
DOI: 10.1039/c5ra09351a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanoparticle attachment and its toxicity on living lung epithelial cells

Abstract: Since its discovery graphene and its oxidized form graphene oxide have attracted interest in a wide range of applications, which calls for scrutinized studies about their possible toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Furthermore, it was found that the hydrophilic form of GF like GO can form a stable colloid dispersion and thus avoids aggregation, which is the key to easy removal from the application site. However, even though GO are more hydrophilic, some early studies showed that these nanosheets exhibited time and dose-dependent cytotoxicity, and managed to enter into the cytoplasm and nucleus, decreasing cell adhesion, and inducing cell floating and apoptosis [ 54 , 55 , 56 , 57 , 58 ]. Thus, surface functionalization can play a major role in providing GO appropriate vehicles for several therapeutics like drug molecules, and especially anticancer drugs, DNA, genes, antibodies, antibacterial, proteins, etc.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…Furthermore, it was found that the hydrophilic form of GF like GO can form a stable colloid dispersion and thus avoids aggregation, which is the key to easy removal from the application site. However, even though GO are more hydrophilic, some early studies showed that these nanosheets exhibited time and dose-dependent cytotoxicity, and managed to enter into the cytoplasm and nucleus, decreasing cell adhesion, and inducing cell floating and apoptosis [ 54 , 55 , 56 , 57 , 58 ]. Thus, surface functionalization can play a major role in providing GO appropriate vehicles for several therapeutics like drug molecules, and especially anticancer drugs, DNA, genes, antibodies, antibacterial, proteins, etc.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…Confocal Raman spectroscopy is an analytical method which has demonstrated great utility in a wide range of applications in life science applications, such as cancer diagnostics [ 1 ] and—as exemplified in this study—detection of particles inside cells [ 2 , 3 , 4 , 5 , 6 , 7 ]. Some advantages are that the method requires minimal sample preparation, is label free and non-destructive [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, it is possible to collect hyperspectral images of the sample by step-wise measurements of small sample volumes [ 4 , 5 , 6 , 7 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is possible to collect hyperspectral images of the sample by step-wise measurements of small sample volumes [ 4 , 5 , 6 , 7 , 8 , 10 , 11 ]. Each pixel in such a (hyperspectral) Raman image contains a Raman spectrum with chemical information from molecules and crystals with Raman active vibrational modes [ 2 , 3 , 4 , 5 , 6 , 7 , 9 ]. It is possible to simultaneously detect particles inside cells [ 2 , 3 , 4 , 5 , 6 , 7 ] and to use the spectral information to discern organelles without using dyes, fluorescent labels, or microtome sectioning and associated embedding methods [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially prepared quantum dots based on Cd sulfides or selenides without surface treatment for their toxicity are not suitable for biological applications. The toxicity and biosafety materials of carbon nanostructures such as carbon nanotubes, graphene, graphene oxide [1,2], carbon, graphene quantum dots [3], iron oxide, and titanium oxide [4] are intensively under study.…”
Section: Introductionmentioning
confidence: 99%